(untitled) (Research, Society and Development, 2021)
The restriction of the movement of people aiming to control the pandemic by COVID-19 impacted the world. However, traffic accidents remain a public health problem in Brazil. Thus, this study aimed to describe the impact of the COVID-19 pandemic on motorcycle accidents and the profile of those injured in Pernambuco. It is a descriptive, quantitative and retrospective study carried out with secondary data from the Information System on Land Transport Accidents, from VIII GERES in the state of Pernambuco. Year I, pre-covid, from March 2019 to February 2020, and Year II, Covid, from April 2020 to March 2021, were considered. Data were entered in Excel, exported and subjected to statistical analysis in the program Statistical Package for the Social Sciences (SPSS) 22.0., performed the T Test for independent samples and 5% confidence interval. In Year I, there were 6206 accidents and in Year II, 5402. It stood out in number of notifications, in Year I, December 2019 (614); while in Year II, December 2020 (533); however, April and May 2020 had the lowest number of notifications. There was a reduction in the number of motorcycle accidents during the COVID-19 pandemic, possibly due to the social isolation measures adopted. The profile observed was of men, young adults, with hospital discharge within 72 hours, lack of license and helmet. Accidents occurred more frequently on Fridays, Saturdays and Sundays, with emphasis on tipping/overturning; reaffirming the vulnerability of those involved in motorcycle accidents.